Pengaruh Penerapan Model Pembelajaran Kooperatif Tipe Numbered Head Together (NHT) Terhadap Kemampuan Berpikir Kritis Peserta Didik Dalam Pembelajaran Matematika - Islamiah, Fitriah; Majid, Ahmad Farham; Sulasteri, Sri (Alauddin Journal of Mathematics Education, 2025)
This study aims to determine: (1) the description of the implementation of the Numbered Heads Together (NHT) cooperative learning model in mathematics learning for grade X students at MA Madani Alauddin, (2) the description of students’ critical thinking skills, and (3) the effect of applying the NHT cooperative learning model on students’ critical thinking skills in mathematics learning. This research employed an ex post facto design with a quantitative approach. The study was conducted at MA Madani Alauddin with a population of 85 grade X students divided into three classes. The sample consisted of 28 students selected through a simple random sampling technique. The instruments used were an NHT implementation questionnaire to measure the level of model application and an essay test to assess students’ critical thinking skills. The data analysis techniques used were descriptive statistics and inferential statistics in the form of a simple linear regression test. The results of the study indicate that: (1) the implementation of the NHT cooperative learning model among grade X students at MA Madani Alauddin was in the high category with an average score of 65.61, (2) students’ critical thinking skills were also in the high category with an average score of 67.57, and (3) based on the simple linear regression analysis, it was found that t_count > t_table (5.557 > 1.7056) with a significance value of 0.000 < 0.05, thus H₀ is rejected and Hₐ is accepted. This means that there is a significant effect of the NHT cooperative learning model on students’ critical thinking skills in mathematics learning. The contribution of this effect is shown by the coefficient of determination (R²) of 0.543, indicating that 54.3% of students’ critical thinking skills are influenced by the application of the NHT model, while the remaining 45.7% are influenced by other factors outside this study.